Security Sector Reform Narrowing the Gap between Theory and Practice - Schnabel, Albrecht (SSR Papers, 2011)
The persistent gap between theory and practice in SSR can be a source of much irritation and disappointment at failures to implement SSR norms as well as in response to concepts and strategies that seem unhelpfully far removed from local realities. This paper compares ideal-case SSR environments with real-life conditions of implementing SSR. Through offering suggestions for better practice in SSR implementation, it shows that the art of applied SSR can be learned.